Reaching targets in the national cervical screening programme: are current practices unethical?. Issue 3 (June 1998) - Foster, P; Anderson, C M
Abstract : The principle of informed consent is now well established within the National Health Service (NHS) in relation to any type of medical treatment. However, this ethical principle appears to be far less well established in relation to medical screening programmes such as Britain's national cervical screening programme. This article will critically examine the case for health care providers vigorously pursuing women to accept an invitation to be screened. It will discuss the type of information which women would need in order to make an informed decision about whether or not to be screened. The lack of such information in current patient leaflets on the "smear test" will then be documented. Finally, the article will explore possible ways of maximising women's autonomy in relation to the cervical screening programme without sacrificing any of its main benefits.